PENYULUHAN PEMASARAN PRODUK BIJI KAKAO UNGGUL DAN PENGELOLAAN KEUANGAN SEDERHANA PADA KELOMPOK TANI PEMUDA ARIBANG DESA PASIANG - Basir, Indra; Adha, Wahyu Maulid; Yamin, Mujirin M (Universitas Mataram, 2024)
Aribang Village, located in Polewali Mandar Regency, holds significant potential for developing premium cocoa products. However, the Aribang Youth Farmer Group faces challenges in product marketing, financial management, and maintaining the enthusiasm of young farmers to sustain agricultural activities. This community service program aims to enhance the capacity of the farmer group in marketing premium cocoa products, managing business finances efficiently, and maintaining the commitment of young farmers to continue contributing to the agricultural sector. The method employed in this activity is a participatory approach, which involves identifying needs through discussions and observations, preparing educational materials, delivering practical training through lectures, simulations, case studies, and post-activity mentoring. The materials provided cover the criteria for premium cocoa products, cocoa product market networks, and basic financial management. The results indicate that this program has been highly beneficial, with a significant increase in participants' knowledge of marketing and financial management. Participants have begun implementing digital marketing strategies and simple business financial records, which are expected to improve the competitiveness of premium cocoa products in the market. This program successfully achieved its objectives by improving the farmer group’s skills in marketing and financial management. However, further mentoring is needed to ensure the sustainability of the implementation.